The Swedish budget 1984/85 (Stockholm : Ministry of Finance, 1984)
This twenty-second edition of The Swedish Budget contains a summary of the draft budget for the fiscal year 1984/85, with a translation of Budget statement. The main items of government expenditure are presented Ministry by Ministry.
A summary published by the Ministry of Finance.
rpm 20/02/2019
Ref.
Keywords: Budget; Economic history; Sweden